NEED ANALYSIS OF ENGLISH FOR SPECIFIC PURPOSES (ESP) FOR HOTEL AND TOURISM IN THE VOCATIONAL HIGH SCHOOL (A Case Study at Eleventh Grade in One of Vocational High S¬¬chool in Ciamis) - Desi Yuniarti (Journal of English Education Program (JEEP), 2014)
This paper reports the need analysis of English for specific purposes (ESP) for hotel and tourism in the vocational high school. This study was aimed at finding out the English Specific purpose material design that taught to students in vocational high school of hotel and tourism major and students’ needed of English specific purpose material to be used in the field. Hutchinson and Waters (1987, p. 59) says that “needs analysis or "target situation needs analysis" is "in essence a matter of asking questions about the target situation and the attitudes towards that situation of various participants in the learning process". In collecting the data regarding the research question above, the writer conducted the study by gaining qualitative research with case study as the research design applied by the writer. This research conducted in a class of eleventh grade which consisted of 30 students in one of vocational high school in Ciamis, West Java. In addition, to collect the data needed, the writer used the interview and questionnaire as the instrument used. The data from interview were analysed by classifying, interpreting and commenting the results of the interview in chapter four. In analysing the questionnaire the writer used the display data interpretation based on the percentage of the computation. The data were displayed in 10 tables completed with the description and conclusion from each item. Based on the finding, most of the 76.70% students responded strongly agree that an English specific purpose is the material that needed for their major. Based on these findings, the writer concluded that the students’ of hotel and tourism needed English specific purposes material for their major. The English specific purposes teacher must have the ability to arrange the appropriate materials and adapted it with the students’ needs of each major. Based on these findings the writer recommended, English for specific purposes can be an effective in teaching English to students at hotel and tourism in vocational high school to enhance students’ language need.